The effect of Transactive Memory System on Team Performance with Rregard to Exploitative Learning Strategy and Strategic Orientations - vahid khashei; Mohammad reza daneshvar (مطالعات مدیریت بهبود و تحول, 2016)
Based on organizational learning theory, the main objective of this study was to examine the relationship between transactive memory systems, Exploitative learning and team performance with regard to the role of moderator strategic orientations in the knowledge-based companies. This study performed at Niroo Research Institute in Tehran. The philosophy of the research is positivism and the strategy is surveying. Therefore, after reviewing the literature and designing the conceptual model, a questionnaire consisted of 29 questions presented to staff members. Then, the data were gathered and analyzed through correlation matrix, structural equation model and fitness test. The results of the data analysis show that transactive memory systems has a significant impact on Exploitative learning, Exploitative learning has a significant impact on team performance and also strategic orientations moderates relationship between Exploitative learning and team performance and in other words, strategic orientations will strengthen the relationship between exploitative learning and team performance